Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/srep42879
|View full text |Cite
|
Sign up to set email alerts
|

Early hepatitis B surface antigen decline predicts treatment response to entecavir in patients with chronic hepatitis B

Abstract: Early declines in serum hepatitis B surface (HBsAg) levels, their optimal cutoffs, and association with therapeutic endpoints in chronic hepatitis B (CHB) patients receiving entecavir treatment remain unclear. We prospectively enrolled 529 patients (195 hepatitis B e antigen [HBeAg]-positive and 334 HBeAg-negative) with a median treatment duration of 49.2 months. Median HBsAg levels declined significantly in both groups at Month 3, but only at Months 6–12 in the HBeAg-negative group. Both groups exhibited a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The results of the current study have shown that timely re‐treatment in all 16 patients with increasing/increased qHBsAg prior to re‐treatment (Pattern I) not only improved hepatitis and rescued the impending/ensuring hepatic decompensation but also led to ‘rapid HBsAg decline’, a reported predictor for achieving qHBsAg <100 IU/mL (5.8‐fold) and HBsAg loss (8.2‐fold) during 5‐year ETV therapy . The four patients with further increase of ALT 1‐2 weeks after starting re‐treatment might develop hepatic decompensation if re‐treatment were delayed, as observed in patient 12 (Figure B).…”
Section: Discussionmentioning
confidence: 66%
“…The results of the current study have shown that timely re‐treatment in all 16 patients with increasing/increased qHBsAg prior to re‐treatment (Pattern I) not only improved hepatitis and rescued the impending/ensuring hepatic decompensation but also led to ‘rapid HBsAg decline’, a reported predictor for achieving qHBsAg <100 IU/mL (5.8‐fold) and HBsAg loss (8.2‐fold) during 5‐year ETV therapy . The four patients with further increase of ALT 1‐2 weeks after starting re‐treatment might develop hepatic decompensation if re‐treatment were delayed, as observed in patient 12 (Figure B).…”
Section: Discussionmentioning
confidence: 66%
“…Low pre-treatment HBsAg levels were significantly associated with HBsAg loss, particularly in hepatitis B e antigen (HBeAg)-positive patients [ 16 ]. Furthermore, several pieces of evidence suggest that on-treatment HBsAg decline was able to predict HBsAg seroclearance, both in HBeAg–positive and –negative patients [ 17 , 18 , 19 ]. However, these results predominantly derive from studies involving Asian patients infected with genotypes B and C. To date, in HBeAg–negative Caucasian patients under long-term treatment with NAs, the predictive value of HBsAg kinetic is less clear [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients receiving NA treatment, HBsAg quantification may help to predict clinical outcomes. HBsAg levels of < 3000 IU/mL at the baseline combined with HBsAg declines of ≥ 75% from the baseline could predict the eventual loss of HBsAg[ 14 ]. An HBsAg reduction of > 1 log IU/mL could reflect improved immune control[ 12 , 15 ], and a reduction of ≥ 0.5 log IU/mL after 6 mo of treatment had a high negative predictive value for HBsAg seroclearance[ 16 ].…”
Section: Introductionmentioning
confidence: 99%